Professions and Professionalism A Research Overview - Dent, Mike (State of the Art in Business Research Series, 2023)
This shortform book provides a critical synthesis of research on professions and professionalism from an international perspective, highlighting the key opportunities and challenges as a field of scholarship, practice and policy